(untitled) (Nigerian Journal of Technology, 2017)
Synthesis of zeolitic materials from mineral ores, encounter serious challenges due to the presence of inherent impurities with the tendencies of inhibiting formation of desired products. Structure directing agent (SDA) though helps to mitigate this effect, but impact negatively on the environment. Zeolite ZSM11 is a promising catalyst that finds application in area not limited to benzene alkylation, gasoline formation from methanol, conversion of low density polyethene into hydrocarbon, etc. Accordingly, this work present successful synthesis of zeolite ZSM11 from kaolinite clay, seeded with NaY type zeolite and aged for 3-11 days, in an organic template free condition. The used kaolinite clays were sourced from two different mines in Nigeria, namely; Kankara and Onibode. They were both subjected to beneficiation, calcinations, dealumination and the gels formed, had molar composition of 9Na2OX30SiO2XAl2O3X225H2O. The raw, intermediate and final products were fully characterized using XRD, XRF, BET and SEM/EDX. The prominent XRD peaks for ZSM11 were noticed for Kankara based sample aged for 11 days with seeding/dealuminatedmetakaolin ratio of 0.2wt% having increased crystallinity and purity as crystallization time increases. Seeding/metakaolin ratios of 0.1, 0.15, 0.25 and 0.3 wt% led to formation of composite material, excluding ZSM11. The morphological analysis gave the shape attributed to ZSM11 and the specific surface area was determined to be 412 and 450m2/g, for Kankara and Onibode based products, respectively. http://dx.doi.org/10.4314/njt.v36i2.17